2018
DOI: 10.5513/jcea01/19.2.2148
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and interrelationships of soybean [Glycine max (L.) Merrill] yield components during dry and humid seasons

Abstract: Global climate changes have caused a significant weather oscillation. The objectives of this study were to determine the influence of weather conditions on the association of soybean seed yield and yield components, to find out the magnitude and effect of each component and their reaction to environmental stress. Seventy-four soybean varieties from nine geographical origins were studied during two seasons (2015 with less rainfall and increased temperatures and 2016 with increased humidity and moderate temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
(10 reference statements)
1
1
0
Order By: Relevance
“…A weak correlation of the positive direction (r = 0.376*) was determined in 2015 between the yield and a protein concentration (Graph 1c). The similar results were report by Esmaili et al (2012) and Varnica et al (2018) in their research.…”
Section: Graph 1 the Correlations Between An Oil Concentration And Tsupporting
confidence: 92%
“…A weak correlation of the positive direction (r = 0.376*) was determined in 2015 between the yield and a protein concentration (Graph 1c). The similar results were report by Esmaili et al (2012) and Varnica et al (2018) in their research.…”
Section: Graph 1 the Correlations Between An Oil Concentration And Tsupporting
confidence: 92%
“…Demirtaş et al (2010) concluded that the NSP is a yield component most sensitive to the stress during the seed growth. The NSP has the highest correlation coefficient and a high and positive effect on the yield, so the selection of high-yielding genotypes based on this trait can be performed directly disregarding the alternating weather conditions (Varnica, 2018). Irrigation, year, and their interaction did not have a statistically significant effect on the TSW (g), but, according to the obtained data, the lowest average TSW (g) was attained in the control treatment (I1) in each examined year.…”
Section: Resultsmentioning
confidence: 99%
“…Plant seed weight is the most important morphological character in finding the best plant from a study [12]. The result shows that the seed weight per plot and the best soybean yield potential were found in Kipas Merah, mutant lines A 1 and A 11 .…”
Section: Fertilizer Analysismentioning
confidence: 97%